Incidence of human rabies following bite or exposure to laboratory confirmed rabid animals - Sandhu, Kanwarpreet S.; Bawa, Pahul K.; Sandhu, Bhupinder S. (International Journal Of Community Medicine And Public Health, 2024)
Background: Rabies is one of the important endemic fatal zoonotic viral disease afflicting humans and animals in Punjab, India. The present study investigated the incidence of rabies in humans bitten/exposed to laboratory confirmed rabid animals, as well as incidence after use of vaccine or rabies immunoglobulin (RIG) and clinico-epidemiological studies. Methods: A study was conducted during August 2021 to September 2022 on forty (40) rabies suspected animals presented to diagnose rabies by direct fluorescent antibody test (dFAT) at rabies diagnostic laboratory (RDL), Guru Angad Dev Veterinary and Animal Sciences University (GADVASU), Punjab, India. A detailed questionnaire was prepared for obtaining information about exposure/bite of humans by rabid animals, death of humans, demographic and epidemiological information of victims. Results: Out of total forty (40) suspected rabies cases, 30(75%) were found positive for rabies by dFAT. Laboratory confirmed rabies (LCR) incidence was 60.80% and 21.73% in stray and pet dogs, respectively. All pet dogs were vaccinated but no stray dog was vaccinated. The LCR incidence in buffaloes and cattle was 77.77% and 100%, respectively. Further in humans exposed to rabid animals (59), males were at more risk than females. The human rabies incidence was 3.38% (2/59). Highest incidence of dog bites in adult males on lower limb was observed from urban stray dogs (60.80%) followed by children. Post exposure vaccination was given to 98.3% humans exposed to rabid animals. Human’s rabies in two cases was due to no vaccination or RIG. Conclusions: Vaccination is an important step in controlling rabies in India. There is a need for integrated and comprehensive management of street dogs and bite management.